THE EFFECT OF INTEREST RATES ON THE DEMAND FOR MULTIPURPOSE LOAN (KSG) AT PT. BANK PERKREDITAN RAKYAT HASAMITRA DAYA MAKASSAR CITY BRANCH - Devi Adnyaswari Ngabe Joyti; Agung Widhi Kurniawan; Nurman; Anwar; Andi Mustika Amin (Transpublika Publisher, 2023)
Banks play a crucial role as financial institutions by collecting and distributing public funds to support national development. Conventional banks primarily generate income through interest charged on loans provided to borrowers. This study aimed to investigate the impact of interest rates on the demand for multipurpose loan (KSG) at PT. Bank Perkreditan Rakyat Hasamitra Daya, Makassar City Branch. The variables considered in this study are interest rates and the demand for multipurpose loans. The population for this study consists of all interest rate data and credit request reports for multipurpose loans at PT. Bank Perkreditan Rakyat Hasamitra Daya, Makassar City Branch. The sample includes interest rate data and credit request reports for multipurpose loan at PT Bank Perkreditan Rakyat Hasamitra Daya, Makassar City Branch, from 2015 to 2022, covering each quarter. The data collection techniques employed in this study are documentation and interviews. The analysis used to determine the relationship between the independent variables and the dependent variable includes simple linear regression, classical assumption tests, and hypothesis testing. The results of the regression equation for the impact of interest rates on the demand for multipurpose loans are as follows: Y = 17,337,852 - 75,073 X. Based on these findings, interest rates do not exhibit a significant effect on the demand for multipurpose loans. The influence of interest rates on the demand for multi-purpose credit at PT. Bank Perkreditan Rakyat Hasamitra Daya, Makassar City Branch, accounts for 38.4%. The remaining 61.6% is influenced by other factors not examined in this study.